Labor arbitration reports awards of arbitrators, reports of fact-finding boards, court decisions on labor arbitrators. - Bureau of National Affairs (Washington, D.C.). (Washington, D.C. Bureau of National Affairs, 1946)
Semiannual
Cover title, v.1- : Labor arbitration reports; dispute settlements.
Key, with directory of arbitrators.
Labor arbitration cumulative digest and index with table of cases and directory of arbitrators.
Subtitle varies.
Supersedes War labor reports.
Vols. 1-10, 1946-48. 1 v.
Keywords: Arbitration, Industrial -- United States -- Cases